OS PROCESSOS RESTAURATIVOS EM CONFLITOS ESCOLARES - Santos, Elis de Castro Benedito dos (2014)
A school is an institution in the society and therefore reflects your symptoms, including violence, which generally has been institutionalized, being perceived as natural and unchangeable, and the manner in which it has been treated by the school only perpetuates. Commonly the resolution of conflict permeates a sense of justice linked to punishment and obedience, there is always a proportional or no relationship between the act and its sanction, being the focus on crime, in the other words, retributive justice. The proposed restorative justice, by contrast, aims at the exact opposite, because if not fixed in punishment and revenge, but the restoration of relationships and appreciation of all involved, by means of restorative circles. These inserts the facilitator and participants. Initially with a presentation of the functioning of the circle. After all, this mode of organization is wrapped in a sacred aura, where everyone prepares for the restitution, since we should be willing to be reconciled. Circles can hear and talk through the talking stick that circulates, who is in his power tells his version of the story without stigmata of victims or offenders, by retelling and listening to the positioning of the other, there is the establishment of new bond. From this formation, subjects can seek consensual solutions to restore relationships, heal the individual needs and eliminate conflicting disputes. The emphasis on accountability of individuals in a society that delegates responsibilities in research promoted the need for discussion of the concepts of guilt and shame as repairing agents. Has the objective to describe experiences examining the use of restorative processes in promoting conflict resolution in school. The study consists of a sample of four cases involving teenagers in school conflicts, which were analyzed qualitatively, considering the subjectivity involved in the reports. Therefore, this work shows that the use of restorative practices in dealing with school conflicts is a possibility of intervention that works to improve the environment and the school acquaintanceship, promoting learning and knowledge exchange, valuing the different tolerance and the possibility of listening , including the conflict in a positive way, abdicating punitive behaviors, but mostly restoring relationships. In this work it was possible to understand that this institutionalized violence, naturalized and reproduced in school, and that breaks this chain to understand the causes of school violence, promoting the replacement of violence by dialogue and by so many other possible answers. Understand conflict as inherent to relationships and how to address the possibility of learning, the managing from the perspective of restorative justice, promotes a multiplier network of peace, in which students disseminate their families and the community these new visions. Repair, restore, reinstate, restore, recover, rebuild, restore. The beauty of this idea, this new paradigm which appropriates this research is the human ability to remake itself, to reinvent itself. Understanding the opportunity to restart, satisfying needs and offsetting losses, is to validate humanity itself.